Analisis Penyebab Terjadinya Kandas KMP Agung Samudra XVIII saat Masuk Pelabuhan Gilimanuk - Vanesha Arda Exstakarisma; Bruce Rumangkang; Nurul Hatifah (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
Shipping accidents, particularly ship grounding incidents, remain a major concern in maritime transportation because they may threaten navigational safety, disrupt port operations, and cause economic losses. Harbor waters with narrow channels, shallow depths, and unpredictable environmental conditions require ship officers to maintain high levels of accuracy and coordination during maneuvering activities. This study examines the factors that caused the grounding of KMP Agung Samudra XVIII while approaching Gilimanuk Harbor. The research employed a qualitative descriptive approach through direct onboard observation, interviews with the master, second officer, helmsman, and chief engineer, as well as analysis of operational records and incident documentation. The collected data were analyzed by identifying the relationship between operational conditions and the actions taken by the ship’s crew before the accident occurred. The findings reveal that the grounding incident was not caused by a single factor, but rather by the interaction of environmental conditions, human factors, and technical issues. Strong sea currents and wind pressure significantly affected the vessel’s maneuverability during harbor entry. In addition, delayed responses from the officer on watch and insufficient communication with the master reduced the effectiveness of navigational decision-making. Technical disturbances in the steering system also contributed to the vessel’s inability to maintain a safe course. As a result, the ship drifted outside the intended navigation lane and eventually ran aground. The study highlights the importance of improving bridge team coordination, strengthening emergency response procedures, and ensuring the reliability of steering equipment in order to minimize the possibility of similar maritime accidents in harbor areas.